Contractual Farming Arrangements, Quality Control, Incentives, and Distribution Failure in Kenya's Smallholder Horticulture: A Multivariate Probit Analysis. Issue 4 (1st March 2016) - Kariuki, Isaac Maina; Loy, Jens‐Peter
ABSTRACT: With the rapid growth of horticultural value chains, the use of contractual farming arrangements, strategies of quality control (farm audits/crop rejections), pricing incentives, and distribution efficiencies (crop collection arrangements) are increasingly breaking market barriers, for example, private standards, certification, traceability, and supply reliability in developing countries. Cognizant of market access, farm produce value, sustainable production, and reduction of postharvest losses, this paper investigated whether farm size, schooling, producer price, farm visits, and social capital networks condition these strategies. The results show that use of written contracts is conditioned by farm sizes, more extension, and number of producer groups (PGs) while farm certification is positively predicted by farm sizes, more extension, number of sellers in the village and seasons with the same buyer. However, certification is less responsive to producer prices. Crop rejections are predicted to be less depending on a farmer's education, number of PGs, and the producer price but are more likely to increase the more the number of sellers. Further, the results show that a forward pricing incentive is highly correlated with higher producer prices, more extension, and number of seasons with the same buyer. Finally, uncollected produce at harvest is likely to decrease with farm sizes, more education and extension, higher producer price, number of PGs, and seasons with the same buyer but is more likely to increase the higher the number of sellers. Implications are made. [EconLit citations: L14; Q13].